The Malcolm Baldrige Award 수상 의료기관 비교연구: 2007-2016년 - 이돈희; Donhee Lee (品質經營學會誌, 2018)
Purpose: The purpose of this study is to provide academic and practical implications based on the analysis results of similarities and differentiation of Malcolm Baldrige National Quality Award (MBNQA) in healthcare institutes from 2007 to 2016. Methods: This study examined the characteristics and similarities, the changes made for the most importantly considered, a degree of improvement of patient satisfaction, and employee retention rate of the MBNQA awarded 8 healthcare institutes announced by NIST during the period of 2007-2016. Results: First, the MBNQA awarded 8 healthcare institutes that maintained and implemented effective plans for a long period of time to improve the quality of care services. Second, these organizations were selected among the top 10% of the institutional evaluations in the medical field in the United States. Third, they have tried to continuously improve patient and potential customer and employee satisfaction. Fourth, it is shown that the quality improvement efforts have made long-term and continuous improvement efforts on average 4-5 years. Lastly, the increased number of patients and the improved organizational performance are twice higher than those of other healthcare institutions. Conclusion: The results of this study suggest that common and differentiation strategies of healthcare institutions should be a good benchmarking model for other competitive healthcare institutions.